Scrap tire technology and markets - Clark, Charlotte; Meardon, Kenneth; Russell, Dexter (Noyes Data Corp., 1993)
This book is presented in two parts. Part I covers the problems associated with scrap tires and identifies existing and potential source reduction and utilization methods that may be effective in solving the scrap tire problem. Barriers to increased utilization and options for removing the barriers are indentified and evaluated. Part II provides information on the use of whole, scrap tires and tire-derived fuel (TDF) as combustion fuel, and on the pyrolysis of scrap tires.
Keywords: Tires -- Recycling.; Recycling (Waste, etc.) -- United States.; Waste products as fuel -- United States.; elektronické knihy; electronic books